Experimental and Numerical Investigation of The Behavior of Screen Grid ICF Walls - El Maghraby, Yosra Hesham (AUC Knowledge Fountain, 2014)
The current research addresses Screen Grid ICF walls, an innovative system that combines structural strength and sustainability. The system however is still in its infancy with relatively few researches and yet not acknowledged by several design codes. The aim of this work is to further gain knowledge in the structural behavior of SGICF walls that will lead to introducing design guidelines. To accomplish this, a test program was prepared and performed. Nonetheless, the experimental program did not entirely address every aspect required to deeply understand the structural behavior of the new system. Finite Element Modeling was performed in order to create a reliable model, validated by the experimental results, on which future intensive parametric study can be performed The monotonic loading experimental program was designed to investigate some test parameters; connection of the wall panel to the footing (dowel effect), grid size/ percentage of perforation, steel bars distribution, reinforcement ratio, use of steel fibers in the concrete mixture, effect of openings and opening sizes. The cyclic loading experimental program was performed to simulate earthquake action. Results of the cyclic loading test program indicated the energy dissipation capacity of the tested walls as well as their stiffness degradation under this type of loading. Finite Element Modeling was performed using ANSYS 12.0. Four models were built representing the four different configurations in the test program. The models produced were numerically tested under combined axial load and in plane monotonic load application. Results of this work indicate that connection of the wall to the foundation beam plays a vital role in the performance of a SGICF wall. Increasing the grid size makes the action of the SGICF wall more like a frame and reducing it makes the wall behave more like a shear wall. Removal of steel bars from designated areas does not affect the lateral load carrying capacity and enhances the ductility. Reducing the size of the steel bars below $12 negatively affected the SGICF wall behavior. Presence of steel bars in the concrete mix enhances the behavior of the wall. Presence of openings reduces the lateral load carrying capacity of the wall. The mode of failure and cracking pattern were affected by the variation in the grid size, presence of openings and reduction of steel bar size. SGICF walls demonstrate a stiffer behavior under cyclic loading than under monotonic loading yet, can carry lower lateral load. The opening size affects the stiffness degradation and the energy dissipation capacity of the SGICF wall. The FEM generally showed good correlation with the experimental results however the program could not model the crack openings in two of the models produced and thus did not correctly represent the actual displacement.